Opak and Bogowonto Coastal Inlet Sand Spit Morphodynamics using Landsat and Sentinel Satellite Images - Rizal Fadlan Abida; Totok Suprijo; Budhy Soeksmantono (Jurnal Segara, 2022)
Sand spits are elongated sand deposits on the beach that often form at the inlet or the headland’s tip. The hydrodynamics of the river flow, waves, storm surge, and tide affect the sand spit formation, which was created by the longshore transport along the coast. Bogowonto and Opak inlets are located in southern coastal Java facing directly to the Indian ocean where micro-tidal, waves, and river flow affecting both inlets, are chosen for this case study. Morphodynamics analysis of sand spit using Landsat 7 and 8, Sentinel 2 image from 2000 to 2020, coastline identification using Modified Normalized Different Water Index (mNDWI). In November 2007 and October 2013, Opak Inlet migratory routes were detected, and closures related to the east season occurred at both of them. Inlet tend to close occur on east season during July until November.